Fate's edge - Andrews, Ilona. (Andrews, Ilona. Edge novels ;, 2011)
Audrey Callahan tries to leave her disreputable past in the Edge behind and lead an honest life, until her brother gets in trouble and she is forced to work with Kaldar Mar, a jack-of-all-trades who has some unusual talents.